Paternal Depression in the Postnatal Period and Early Father–Infant Interactions - Sethna, Vaheshta (Parent Sci Pract, 2015)
Objective. Paternal depressive disorder is associated with adverse effects on child development. One possible mechanism for this is through the effects of the disorder on parenting capacities. The link between paternal depression and father–infant interactions was investigated at three-months postpartum. Design. Major depressive disorder was assessed in N = 192 fathers using a structured clinical interview (SCID). Altogether, 54 fathers met criteria for depression, and 99 fathers were categorized as non-depressed. Observational assessments of face-to-face father–infant interactions were conducted in an infant-seat setting and a floor-mat setting. Associations between paternal depression and father–infant interactions were analyzed. Results. Paternal depression is associated with more withdrawn parental behavior in interactions on the floor-mat. There were few other differences in observed interaction between depressed and non-depressed fathers. Conclusions. Fathers with depression may be more withdrawn, displaying less verbal and behavioral stimulation during interactions with their young infants. They may initiate a pattern of parenting that remains compromised, potentially affecting their children’s development.